A New Worldwide Measure of Happiness Explains National Differences in Suicide Rates and Cigarette Consumption. (October 2019) - Minkov, Michael; Schachner, Michael; Sanchez, Carlos; Morales, Oswaldo
Studies of happiness or subjective well-being (SWB) employ a variety of conceptualizations and item formats. Some authorities prefer to focus on the cognitive or evaluative component of SWB in studies of national happiness, and consider the affective component a lesser priority. However, we show that the latter component has unique and important predictive properties. We measured the stable element of the affective component (being "usually happy and in a good mood") in 44, 096 respondents recruited probabilistically from 56 societies (nations and some ethnic groups), from all inhabited continents. Consistent with previous studies, we obtained the highest positive affect scores in the nations of northern Latin America and Africa, whereas the highest percentages of respondents "rarely in a good mood" were recorded in East Asia, Russia, Italy, and the Arab world. Our happiness measure is a significant negative predictor of national suicide rates and cigarette consumption, after controlling for other plausible predictors, including other SWB measures from the World Values Survey, Veenhoven's World Database of Happiness, and climate and socioeconomic variables.